120 Sinar Ecer participants congregated in UMP Gambang Campus - UMP, PNC
A total of 120 children whose families were involved in the Pekan Agropolitan project took part in a two-day Sinar ECER Innovation and Creativity Day organised by Universiti Malaysia Pahang (UMP) on January 14 and 15, 2012.